Analisis Perbandingan Return Saham Pada Saat Vaksin Sinovac Beredar dan Pfizer Beredar - RINI IRAWAN (EKBIS (Ekonomi & Bisnis), 2021)
Abstract. This study aims to analyze the stock return comparison period when the Sinovac vaccine and Pfizer vaccine entered; the stock used is the Composite Stock Price Index, the period from March 25, 2021, to November 12,2021. In this study, the analysisis was carried out by calculating the stock return of the JCI, which was then continued by calculating it using the Independent sample t-test difference on SPSS 25. The result of the return calculation show that stock returns when Sinovac entered with the stock return when the Pfizer vaccine was in circulation did not have a significant difference.